Ontogeny and taxonomy of the hadrosaur (Dinosauria, Ornithopoda) remains from Basturs Poble bonebed (late early Maastrichtian, Tremp Syncline, Spain). - Víctor Fondevilla; Fabio Marco Dalla Vecchia; Rodrigo Gaete; Àngel Galobart; Blanca Moncunill-Solé; Meike Köhler (PLoS ONE, 2018)
The lower Maastrichtian site of Basturs Poble (southern Pyrenees, Spain) is the first hadrosaur bonebed reported from Europe. It is an accumulation of disarticulated lambeosaurine skeletal elements, possibly belonging to Pararhabdodon isonensis. The sample shows high intraspecific morphological variability among many skeletal elements, suggesting the need for caution in choosing characters for phylogenetic analyses. Juvenile to adult individuals are represented in the sample, while hatchling remains are absent. Bone histology reveals that juveniles are over-represented and that the youngest individuals represented by tibia specimens were two years old. Adult individuals, with tibiae 550-600 mm long, were 14-15 years old when they died. However, individual variation in tibia length at skeletal maturity occurs within the sample, so individual maturity cannot be assumed on the basis of bone size alone. The Basturs Poble bonebed occurs within the upper part of the C31r magnetochron. Thus, lambeosaurine hadrosaurids were already present and abundant in the Ibero-Armorica Island at the end of the early Maastrichtian and P. isonensis spans the upper part of the lower Maastrichtian to the upper part of the upper Maastrichtian (upper part of C31r-lower part of C29r).